2018
DOI: 10.1097/shk.0000000000001098
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Rich Saline Regulates Intestinal Barrier Dysfunction, Dysbiosis, and Bacterial Translocation in a Murine Model of Sepsis

Abstract: Bacterial translocation is a major cause of multiple organ dysfunction syndrome in critical illness, and its management is an important therapeutic strategy. In this study, we focused on the key factors responsible for bacterial translocation including the intestinal microbiome and investigated the impact of molecular hydrogen therapy as a countermeasure against bacterial translocation in a murine model of sepsis. The experimental protocols were divided into the sham, saline treatment (control), and hydrogen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 33 publications
0
32
1
Order By: Relevance
“…In this study, HRS decreased the Chiu score and the expression levels of serum IFABP, TNFα and IL-1β, which indicated that HRS could alleviate the intestinal epithelial cells injury within hours after ischemia-reperfusion. Ikeda et al have found that there were no significant differences between the control and H 2 groups in the analysis of mRNA expression of tight junction proteins ZO-1 and occludin at 24 h after cecal ligation and puncture [43]. In our study, however, compared with the I/R group, the application of HRS could maintain the expression levels of intestinal epithelial TJ proteins occludin and ZO-1.…”
Section: Discussioncontrasting
confidence: 75%
“…In this study, HRS decreased the Chiu score and the expression levels of serum IFABP, TNFα and IL-1β, which indicated that HRS could alleviate the intestinal epithelial cells injury within hours after ischemia-reperfusion. Ikeda et al have found that there were no significant differences between the control and H 2 groups in the analysis of mRNA expression of tight junction proteins ZO-1 and occludin at 24 h after cecal ligation and puncture [43]. In our study, however, compared with the I/R group, the application of HRS could maintain the expression levels of intestinal epithelial TJ proteins occludin and ZO-1.…”
Section: Discussioncontrasting
confidence: 75%
“…21 Studies have confirmed that hydrogen-rich saline can regulate intestinal barrier dysfunction and bacterial migration in mouse models of sepsis. 22 Previous studies have shown that the loss of barrier function of intestinal epithelial cells may be caused by the destruction of epithelial cells and severe metabolic injury caused by sepsis. 23 These effects may be related to the disturbance of intestinal microbiota after sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated conflicting results regarding specific inflammatory pathways, reflecting the complexity of the relationship between the gut microbiome and the immune system. For example, in a mouse model of Streptococcus pneumoniae sepsis, pre-treatment with oral antibiotics prior to sepsis onset was associated with lower levels of lung TNF-α, a pro-inflammatory cytokine [25], whereas others have shown the opposite effect of gut microbiome depletion on TNF-α [21,22,[37][38][39]. Despite differences in specific cytokine expression between studies, the overall effect of alteration of normal gut microbiome structure prior to sepsis onset appears to be a more robust inflammatory response to sepsis [21,22,25,[37][38][39][40][41].…”
Section: Altered Immune Responsementioning
confidence: 99%